Analisis Pengelolaan Aset Tetap Pada Badan Pengelolaan Keuangan dan Aset Daerah di Kabupaten Jepara - Aida Nahar; Ambar Sari Hadiyanti (Jurnal Rekognisi Akuntansi, 2018)
Assets are one of the important elements that must be managed properly, because in the administration of local government assets are needed to support the success of operational activities. The purpose of this study was to find out that the management of fixed assets in Jepara Regency was in accordance with the procedures, to find out that the management of fixed assets in Jepara Regency was in accordance with the Regulation of the Minister of Home Affairs Number 19 of 2016, and to find out what obstacles were experienced in reporting fixed assets in Jepara Regency. Jepara Regency. The research method used is descriptive qualitative research. The data used in this study are subject data. Sources of data obtained from interviews, observation and documentation. The results of the study show that the implementation of fixed asset management carried out by the BPKAD of Jepara Regency has so far been carried out thoroughly in accordance with Permendagri Number 19 of 2016 concerning Technical Guidelines for the Management of Regional Property. By using a conformity analysis of the application of legislation regarding the implementation of fixed asset management carried out by Jepara Regency with Permendagri No. 19 of 2016 so far there are still things that are not in accordance with the laws and regulations, in this case the making of a maintenance card, which is related to the results of the maintenance that has been carried out. However, this does not cause the asset management to be hampered.